2015
DOI: 10.3171/2014.11.spine14624
|View full text |Cite
|
Sign up to set email alerts
|

Mapping occipital bone thickness using computed tomography for safe screw placement

Abstract: OBJECT Safe and effective insertion of occipital bone screws requires morphological analysis of the occipital bone, which is poorly documented in the literature. The authors of this study present morphological data for determining the area of screw placement for optimal internal fixation. METHODS The subjects of this institutional review board-approved retrospective study were 105 individuals without hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Therefore, cortical thickness and the space between the cortex and the canal should be carefully evaluated prior to surgery because sufficient cortical thickness contributes to bony stability and prevention of IAN damage following fixation [ 4 , 24 – 26 ]. As mentioned earlier, the vital role of cortical thickness in bone surgery has been previously demonstrated, and it can thus be considered that cortical thickness affects the surgical procedure and postoperative stability [ 11 , 14 , 15 , 19 , 20 , 27 , 28 ]. Studies have indicated the importance of assessing cortical thickness to determine the optimum anatomical location for fixation [ 15 , 27 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, cortical thickness and the space between the cortex and the canal should be carefully evaluated prior to surgery because sufficient cortical thickness contributes to bony stability and prevention of IAN damage following fixation [ 4 , 24 – 26 ]. As mentioned earlier, the vital role of cortical thickness in bone surgery has been previously demonstrated, and it can thus be considered that cortical thickness affects the surgical procedure and postoperative stability [ 11 , 14 , 15 , 19 , 20 , 27 , 28 ]. Studies have indicated the importance of assessing cortical thickness to determine the optimum anatomical location for fixation [ 15 , 27 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned earlier, the vital role of cortical thickness in bone surgery has been previously demonstrated, and it can thus be considered that cortical thickness affects the surgical procedure and postoperative stability [ 11 , 14 , 15 , 19 , 20 , 27 , 28 ]. Studies have indicated the importance of assessing cortical thickness to determine the optimum anatomical location for fixation [ 15 , 27 32 ]. Placement of the plate and screw over the mandibular body should be performed with caution in order to avoid injury to the IAN canal that runs through the structure.…”
Section: Discussionmentioning
confidence: 99%
“…Since the thickest bone area highly overlapped with the areas where the VS was present, we agree with the recommendation from other studies to obtain a preoperative CTA to evaluate both the occipital thickness and morphology of the planned fixation area to identify abnormal VS anatomy to avoid iatrogenic injuries. 14,15 Also, the evaluation of systemic bone quality is warranted to determine the necessity of bicortical screw fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Various techniques were described and used widely; involve the screw placement to the occipital diploic bone [5][6][7][8]. The unique anatomy and function of the region, the perceived high risk of vascular and neurological complications, and the anatomical variations make OCF a challenging procedure.…”
Section: Discussionmentioning
confidence: 99%